2009
DOI: 10.2320/matertrans.mra2008255
|View full text |Cite
|
Sign up to set email alerts
|

Forgeability and Flow Stress of Mg-Zn-Y Alloys with Long Period Stacking Ordered Structure at Elevated Temperatures

Abstract: To develop a forging process for high strength Mg-Zn-Y alloys with a long period stacking ordered (LPSO) structure, the forgeability and flow stress of Mg 97 Zn 1 Y 2 (at%) alloys were investigated with the upsettability test at an initial strain rate of 0.55 s À1 . As-cast and extruded Mg 97 Zn 1 Y 2 alloys can be successfully forged without fracture up to 0.5 and 1.0 respectively of average equivalent strain at a forging temperature of 773 K. To remove the influence of the temperature change during upsetting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It has been suggested that kink deformations in the LPSO phase and microstructural refinement in the α-Mg phase occur during extrusion deformation [7]. The tensile yield strength, microstructure, fatigue properties, and thermal sta-bility of extruded Mg 96 Zn 2 Y 2 and LPSO-type Mg alloy have been reported [8][9][10]. Enhancements in the strength of Mg 96 Zn 2 Y 2 alloy by means of extrusion have been investigated and reported by Kawamura et al [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that kink deformations in the LPSO phase and microstructural refinement in the α-Mg phase occur during extrusion deformation [7]. The tensile yield strength, microstructure, fatigue properties, and thermal sta-bility of extruded Mg 96 Zn 2 Y 2 and LPSO-type Mg alloy have been reported [8][9][10]. Enhancements in the strength of Mg 96 Zn 2 Y 2 alloy by means of extrusion have been investigated and reported by Kawamura et al [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many kink deformation bands were seen to be formed in the LPSO phase, as reported previously. 5,6,[16][17][18][19][20][21]25) The dispersion of the LPSO phase seems to increase with increasing average equivalent strain. Figure 6 shows SEM images of the Mg 97 Zn 1 Y 2 alloys extruded at 623 K with varying average meal flow rate.…”
Section: Microstructurementioning
confidence: 99%
“…where i β is a coupling constant reflecting the strength of the response of walker i to a lateral force. Data on the natural stepping frequency of humans show that the frequencies of a typical group of humans is, on average, peaked at about 1 Hz, with a spread of the order of 0.1 Hz [13]. This average stepping frequency is slightly below the resonant frequency of the lowest order lateral mode of the north span of the Millennium Bridge.…”
Section: Reduced Modelmentioning
confidence: 93%